Association of socio-culture factors with disordered eating behavior: An empirical study on urban young girls of West Bengal, India - Ganguly, Nandini; Roy, Subho; Mukhopadhyay, Susmita (Anthropological Review, 2018)
A shift towards the concept of thin body image is occurring among the urban girls, as an outcome of mass media exposure. A large section of the girls are involved in attaining thin body image which at times develops dissatisfaction over body weight. Body weight dissatisfaction gives rise to the development of body weight concern and disordered eating behavior. The present research aimed to find out the association of socio-cultural factors with disordered eating behavior among a group of urban girls. The study group included 400 girls aged between 14 and 21 years, residing in the city of Howrah, West Bengal, eastern state of India. Information on socio-demographic characteristics, body weight concern, media habits, and family-peer environments was collected using standard pretested questionnaires. A cross-culturally tested questionnaire developed by Srinivasan and colleagues in 1998, was used to measure disordered eating behavior. Bivariate analyses found significant associations between eating behavior and several socio-cultural factors. Multivariate analysis revealed that education level of fathers and birth order of the participants, body weight concern and peers’ influence were the significant predictors of disordered eating behavior of the study participants. Socio-cultural factors have significant associations with the disordered eating behavior of the study participants.